Using the Transversal Admittance to Understand Organic Electrochemical Transistors - Juan Bisquert; Scott T. Keene (Advanced Science)
Abstract The transient behavior of organic electrochemical transistors (OECTs) is complex due to mixed ionic‐electronic properties that play a central role in bioelectronics and neuromorphic applications. Some works applied impedance spectroscopy in OECTs for understanding transport properties and the frequency‐dependent response of devices. The transversal admittance (drain current vs gate voltage) is used for sensing applications. However, a general theory of the transversal admittance, until now, has been incomplete. The derive a model that combines electronic motion along the channel and vertical ion diffusion by insertion from the electrolyte, depending on several features as the chemical capacitance, the diffusion coefficient of ions, and the electronic mobility. Based on transport and charge conservation equations, it is shown that the vertical impedance produces a standard result of diffusion in intercalation systems, while the transversal impedance contains the electronic parameters of hole accumulation and transport along the channel. The spectral shapes of drain and gate currents and the complex admittance spectra are established by reference to equivalent circuit models for the vertical and transversal impedances, that describe well the measurements of a PEDOT:PSS OECT. New insights are provided to the determination of mobility by the ratio between drain and gate currents.